Too big to care : promoting ethics when ethics are not profitable - Shanahan, Doreen E.; Baker, Jeffrey R.; Rapier, Stephen M.; Dodd, Nancy Ellen (London : NeilsonJournals Publishing, 2020)
Beginning in 2002, Wells Fargo began opening fraudulent accounts for unsuspecting customers. Stakeholders at every level either participated in, ignored, or tolerated the bank's behavior that defrauded consumers on a massive scale. These unethical and well-documented schemes spanned more than a decade. Using public sources, this case recounts the events and ethical lapses that unfolded over the multiyear investigation of the Wells Fargo fraudulent accounts scandal and illuminates the general systemic failures of corporate culture and governance, public regulation, and market responses to promote ethical business practices. This case provides the opportunity to consider what means for fostering ethical conduct might exist if a corporation can be big enough and rich enough that civil, criminal, regulatory, and market forces cannot deter unethical corporate practices, and if the market does not punish the corporation for a culture that promotes fraud.
Originally Published InShanahan, D. E., Baker, J. R., Rapier, S. M., & Dodd, N. E. (2020). Too Big to Care: Promoting Ethics When Ethics Are Not Profitable. Journal of Business Ethics Education, 17(1), 221-236. JBEE17-0CS2.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Wells, Fargo & Company -- Case studies; Business ethics -- Case studies; Social responsibility of business -- Case studies